Occurrence of seromucinous borderline tumours in the peritoneal lesions after bilateral salpingo-oophorectomy - Yamada, Taihei (BMJ Case Rep, 2020)
A 65-year-old woman with a previous history of bilateral salpingo-oophorectomy had peritoneal cysts, increasing in size over 15 years and an increasing cancer antigen 19–9 (CA 19–9) level. The size of the cysts eventually reached 86 mm and 70 mm. As malignant transformation of endometriosis was suspected, we performed peritoneal cystectomy and hysterectomy. Histopathology revealed seromucinous borderline tumours (SMBTs) derived from endometriosis. One month after surgery, her CA 19-9 level had decreased. It is rare for SMBT to occur after bilateral salpingo-oophorectomy; surgical management is the best treatment at present.